Camelia - Rosales, Carmen; Dela Rosa, Rogelio; De Leon, Narcisa; De Guzman, Susana Canseco (LVN Pictures, 1949)
Romantic drama between the two main characters played by Carmen Rosales and Rogelio dela Rosa. The film shows love against all odds between the two main characters because the female protagonist diagnosed that she have cancer.